STUDI KRITIS PEMIKIRAN SITI MUSDAH MULIA TENTANG IDDAH PADA KOMPILASI HUKUM ISLAM (KHI) - efendy, noor (An-Nahdhah | Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
This research departs from Siti Musdah Mulia's thoughts as stated in the Couter Legal Draft Compilation of Islamic Law (CLD KHI), that husbands and wives both have equal iddah periods. In relation to the Compilation of Islamic Law in Indonesia, iddah is only intended for wives, the reason is because it is related to female reproduction. Given these differences, it is necessary to examine further the thoughts of Siti Musdah Mulia which often sparks this controversy. This research aims to find out Siti Musdah Mulia's thoughts about Iddah in the Compilation of Islamic Law (KHI). In detail, this objective includes Siti Musdah Mulia's thoughts about women and about iddah as well as Siti Musdah Mulia's methodology regarding the concept of Iddah. This research is library research using a normative theological approach. Through inductive methods and interpretation in data analysis techniques, this research produces the following findings: first, in the Compilation of Islamic Law (KHI) the iddah provisions for women are regulated in a complex way. According to the Compilation of Islamic Law (KHI), iddah is the waiting period and prohibition on marriage for women after their husband dies or divorces them. Second, according to Siti Musdah Mulia, the iddah provisions are not only obligatory for women, but the iddah provisions are also obligatory for men. This opinion is different from the majority of ulama regarding the obligations of iddah. Keywords: Siti Musdah Mulia, Iddah, Compilation of Islamic Law.